Tingkat Kesiapan Penyuluh Pertanian Lapangan (PPL) dalam Pemanfaatan Teknologi Informasi dan Komunikasi di Kabupaten Lampung Selatan - Kinka Endiasa; Dame Trully Gultom; Sumaryo Gitosaputro; Indah Listiana (Fakultas Pertanian, Universitas Lampung, 2025)
Information and Communication Technology (ICT) had been widely implemented by Agricultural Extension Officers (PPL) in South Lampung Regency, and their level of readiness in utilizing ICT was categorized as very ready. This study aimed to analyze the level of readiness of Agricultural Extension Officers in utilizing ICT, as well as the related factors. The research was conducted using a quantitative approach with a survey method targeting PPL in Natar and Candipuro Districts. Data were collected through questionnaires and analyzed using Spearman's rank correlation test. The results showed that the readiness of PPL in utilizing ICT was categorized as very ready, with the following indicator breakdown: optimism and innovativeness were in the very ready category, discomfort was in the ready category, and insecurity was in the less ready category. Factors related to the level of readiness included age, the number of assisted farmer groups, and the availability of facilities and infrastructure. On the other hand, formal education level and years of service did not show a significant relationship.